2014
DOI: 10.1590/1806-9282.60.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Body composition of preschool children and relation to birth weight

Abstract: Body composition of preschool children and relation to Birth weight rev assoc med Bras 2014; 60(2):139-144 139Original articleBody composition of preschool children and relation to birth weight Conflict of interest: noneObjective: to evaluate the relationship between body composition of preschool children suffering from excess weight and birth weight (BW). Methods: probabilistic sample, by conglomerates, with 17 daycare centers (of a total of 59) composing a final sample of 479 children. We used Z-score of Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
1
0
2
Order By: Relevance
“…Ці методики були валідними для практично здорових дітей. Лише кілька когортних досліджень на обмеженому клінічному матеріалі оцінювали можливість застосування розрахункового методу, заснованого на каліперометрії, для оцінки жировідкладення у дітей з хронічною патологією [6][7][8].…”
Section: вступunclassified
“…Ці методики були валідними для практично здорових дітей. Лише кілька когортних досліджень на обмеженому клінічному матеріалі оцінювали можливість застосування розрахункового методу, заснованого на каліперометрії, для оцінки жировідкладення у дітей з хронічною патологією [6][7][8].…”
Section: вступunclassified
“…Asians are known to possess a different amount and distribution of body fat than Caucasians of similar BMI (13,14). Many studies have focused on youth and performed direct measurements of body composition, including skin fold thickness, bioelectrical impedance analysis and the DXA method (15)(16)(17). Our previous studies showed that increases in BMI during preschool childhood are mainly due to greater fat-free mass (predominantly muscle) rather than fat mass based on DXA-measured body composition (17).…”
Section: Introductionmentioning
confidence: 99%
“…o ganho de peso e o risco de obesidade, não observou efeitos diretos na adiposidade41 .RALT42 observou haver uma rivalidade entre a massa muscular e o crescimento em estatura, evidenciando que pode haver uma relação entre uma maior estatura e presença de obesidade entre crianças com menor massa muscular. MACHADO e colaboradores43 em estudos, pode ser importante para identificar diferentes padrões de ganho de peso e potenciais oportunidades para prevenção ou intervenção44 .Considerando que a obesidade vem atingindo a população infantil cada vez mais precocemente, poucos são os estudos no Brasil que investigam a evolução do excesso de peso e da obesidade em pré-escolares e os aspectos da avaliação antropométrica que têm relação com esse desfecho.Assim, observar a evolução dos pré-escolares com excesso de peso bem como identificar os novos casos e os possíveis indicadores antropométricos que se relacionam com o desenvolvimento dessa condição podem ser ferramentas úteis para melhorar os cuidados de saúde da população, de forma a reduzir o surgimento de novos casos e inclusive a prevalência de crianças com excesso de peso, condição que atualmente é tida como um sério problema de saúde pública.Avaliar a evolução do estado nutricional dos pré-escolares e sua relação com seu crescimento em estatura durante o mesmo período. Taubaté, localizado na mesorregião do Vale do Paraíba, dista 123 km da cidade de São Paulo, capital do Estado.…”
unclassified